Evaluation of a clinical pharmacist-led antimicrobial stewardship program in a neurosurgical intensive care unit: a pre-and post-intervention cohort study - Yu, Jing; Liu, Yan; Qu, Ruochen; Wang, Ziyang; Zhao, Yan; Zhao, Yuanyuan; Zhou, Chunhua (Frontiers in Pharmacology, 2023)
Background: Antimicrobial resistance poses a significant challenge in neurosurgical intensive care units (ICU). The excessive use of broad-spectrum antibiotics is closely linked to the emergence and dissemination of drug-resistant bacteria within neurosurgical ICUs. This study assessed the effects of implementing a comprehensive Antimicrobial Stewardship (AMS) program in a neurosurgical ICU setting.Methods: From April 2022 to September 2022, an AMS program was implemented in the neurosurgical ICU. The program involved the regular presence of a pharmacist and an infectious disease physician who conducted prospective audits and provided feedback. To assess the impact of the AMS program, the outcome measures were compared between the AMS period and the six months before AMS implementation (pre-AMS period). The primary outcome was the use of antibacterial agents, including anti-pseudomonal beta-lactams (APBLs), polymyxin, and tigecycline.Additionally, the study evaluated the appropriateness of antimicrobial de-escalation and the susceptibility of Gram-negative bacilli to antimicrobial agents.Results: A total of 526 were included during the AMS period,while 487 patients were included in the pre-AMS period. The two groups had no significant differences in disease severity and mortality rates. During the AMS period, there was a notable decrease in the use of APBLs as empiric treatment(43.92% vs. 60.99%, p < 0.001).Multi-drug resistant organism(MDRO) infections decrease significantly during AMS period(11.03% vs. 18.48%, p < 0.001). The number of prescription adjustment increased significantly in all patients(0 item vs. 0 item, p < 0.001) and MDRO-positive patients(3 items vs. 2 items, p < 0.001) during the AMS period.Additionally, appropriate antimicrobial de-escalation for patients with MDRO showed improvement during the AMS period (39.66% vs. 20%, p = 0.001). Polymyxin utilization also decreased during the AMS period (15.52% vs. 31.11%, p = 0.034).Furthermore, the susceptibility of Gram-negative Bacilli isolates to APBLs was significantly higher during the AMS period.Conclusions: Implementing a comprehensive pharmacist-led AMS program led to a decrease in the use of antibacterial agents. This reduction in usage is significant because it can potentially delay the emergence of bacterial resistance.